Foliar application of iron glutamate improves yield and growth of tomatoes compared to iron sulphate and L-glutamate - Mazhar, M. W.; Akram, R.; Shahid, A.
Tomato (Solanum lycopersicum L.), grown in iron deficient and calcareous soils, exhibits poor growth and yield loss, which may be moderated using biostimulants. A field experiment was conducted to determine the efficacy of the application of iron glutamate (Fe-Glu), iron sulfate (FeSO4), and L-glutamate (Glu)on growth and yield performance. Foliar application included: no treatment (NS), 0.50 percent FeSO4, 1 percent FeSO4, 0.50 percent Fe-Glu, 1 percent Fe-Glu, 0.50 percent L-Glu, or 1 percent L-Glu. Foliar application of 1 percent Fe-Glu increased plant height by 31 percent, shoot fresh weight by 25 percent, root fresh weight by 38 percent, and canopy diameter by 23 percent. Exogenous application with 1 percent Fe-Glu improved the fruit count and overall yield by 57 percent and 44 percent, respectively. There was an increase in fruit length by 20 percent and an increase in fruit diameter by 25 percent, respectively, due to foliar application of 1 percent Fe-Glu. Use of 1 percent Fe-Glu foliar might act as a better biostimulant than conventional sulfate salts in increasing tomato crop performance.
Keywords: SOLANUM LYCOPERSICUM; MINERAL AMINO ACID CHELATES; YIELD; FESO4